2014
DOI: 10.4081/ejh.2014.2254
|View full text |Cite
|
Sign up to set email alerts
|

A simplified immunohistochemical classification of skeletal muscle fibres in mouse

Abstract: The classification of muscle fibres is of particular interest for the study of the skeletal muscle properties in a wide range of scientific fields, especially animal phenotyping. It is therefore important to define a reliable method for classifying fibre types. The aim of this study was to establish a simplified method for the immunohistochemical classification of fibres in mouse. To carry it out, we first tested a combination of several anti myosin heavy chain (MyHC) antibodies in order to choose a minimum nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 27 publications
8
81
0
Order By: Relevance
“…Second, the gene expression was analyzed based on a single skeletal muscle, the TA muscle. TA is composed of predominantly type II fibers, which is also the predominant muscle fiber type in the hind limb muscles of mice . Soleus (SOL) was not used for the analysis due to the fact that mouse SOL contains a mixture of type I and type II muscle fibers, which is in contrast to other mammals (mainly type I muscle fibers) .…”
Section: Discussionmentioning
confidence: 99%
“…Second, the gene expression was analyzed based on a single skeletal muscle, the TA muscle. TA is composed of predominantly type II fibers, which is also the predominant muscle fiber type in the hind limb muscles of mice . Soleus (SOL) was not used for the analysis due to the fact that mouse SOL contains a mixture of type I and type II muscle fibers, which is in contrast to other mammals (mainly type I muscle fibers) .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the data described above were derived from measurements in the gastrocnemius of rats and tibialis anterior of mice, which are composed of both slow-and fast-twitch fibers (55,63). Whether REDD1 possesses a fiber type-specific effect with refeeding remains to be determined.…”
Section: Role Of Redd1 During Physiological Conditionsmentioning
confidence: 99%
“…This variation may be caused by various compositions of muscle fiber type in specific muscles. For instance, TA and EDL contain more fast‐glycolytic type IIb fiber than SOL, which mainly contains slow‐oxidative type I and fast‐oxidative type IIa (42). In addition, it has been revealed that food deprivation could preferentially affect protein turnover in fast‐glycolytic fibers (43, 44).…”
Section: Discussionmentioning
confidence: 99%